THE SHIFTING FUNCTION OF ABDUL MULUK'S TRADITIONAL THEATER: FOLK PERFORMANCE TO AN EXCLUSIVE PERFORMANCE - Wulandari, Iis; N, Sahrul; Asril, Asril (Jurnal Kajian Seni, 2025)
The development of the times made the continuity of Abdul Muluk's traditional theater in Muaro Jambi Regency experience a shift. The shift in art consumption patterns resulted in a shift in the function of Abdul Muluk's traditional theater from folk entertainment to exclusive spectacle. This study aims to analyze the factors causing and the impact of the shift in the function of Abdul Muluk's traditional theater in Muaro Jambi Village, Muaro Jambi Regency, Jambi Province. The research method used is a qualitative method with an art sociology approach based on Janet Wolff's social production theory of art. Data collection techniques used literature study, observation, interviews and documentation. The results showed that this shift occurred due to internal factors, such as the lack of management in theater groups and the lack of regeneration. Meanwhile, external factors include changes in public tastes, the influx of modern entertainment, and the weakening of institutional support and patronage. This shift has had an impact on various aspects, including the duration of performances, changes in stories, and most prominently accessibility, which is now limited. This study provides insights into how traditional arts are adapting to globalization and highlights the importance of support from others.